(untitled) (Al Insyirah International Scientific Conference on Health, 2023)
Bedside Monitorsis a tool used to monitor the patient’s vital signs in the form of heart rate, pulse, blood pressure, temperature, and the shape of the heart pulse continuously.Apart from being used in hospitals, this tool is also used in electromedical laboratories as a tool for clinical practice for electromedical students. All medical devices must be calibrated periodically. In this study, we will discuss how to calibrate the bedside monitor device with the aim of knowing whether the bedside monitor device in the laboratory is suitable for use or not. The research was carried out using work methods set by the ministry of health including physical examination and function of the equipment, electrical safety and measurement of the performance of the device using the suction power parameter. The results showed that the results of the physical inspection and tool function were 10%, electrical safety checks were 30% and performance measurements of NIBP, SPO2.